EDUKASI PAJAK KENDARAAN: INVESTASI LOKAL MELALUI PEMAHAMAN DAN KEPATUHAN PAJAK - Sudianto Sudianto; Mulyadi Mulyadi; Andi Hidayatul Fadlilah; Andi Auliya Ramadhany (Jurnal Abdimas Bina Bangsa, 2024)
In accordance with Law Number 25 of 1999, the Dispenda of Kepri Province was established to carry out regional tax and levy organizations. Through this service, consumers will be able to view vehicle taxes less as a mandate and more as an active way to establish and improve government programs that benefit the community. Action Research with Participation (PAR) As a consequence of the research process, which starts with planning, carrying out actions, and assessing the outcomes of activities, PAR is an action research activity. According to Bapenda of Kepri Province, in order to surpass the target's present level of achievement—despite the fact that it has been reached—it is preferable to get recommendations and input from the outcomes of education and interviews. Online applications must be utilized for tax payment and collection. Because the Digital Age is already here